2017
DOI: 10.1270/jsbbs.17035
|View full text |Cite
|
Sign up to set email alerts
|

Early selection of potato clones with resistance genes: the relationship between combined resistance and agronomical characteristics

Abstract: Cultivating resistant varieties of potato is the most effective and environmentally safe method of protecting against pests and diseases that affect potato crops. Therefore, potato breeding is focused on developing more resistant varieties so that the use of plant health products can be reduced during the cultivation cycle. Resistance to late blight, viruses and nematodes is the most important agricultural requirement. The use of molecular markers allows for the effective selection of resistant genotypes at ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Clones with identified H1 gene had similar starch content, but significantly higher starch yield compared with clones without gene H1 (Milczarek et al 2014). In our next previous work (Milczarek et al 2017), starch content and eye depth were not different among the lines with/without H1. In this study, however, significant differences were observed in these traits.…”
Section: Discussionmentioning
confidence: 59%
“…Clones with identified H1 gene had similar starch content, but significantly higher starch yield compared with clones without gene H1 (Milczarek et al 2014). In our next previous work (Milczarek et al 2017), starch content and eye depth were not different among the lines with/without H1. In this study, however, significant differences were observed in these traits.…”
Section: Discussionmentioning
confidence: 59%
“…Markers linked to resistance genes of economically important diseases and nematodes are useful tools for potato breeding (Asano and Tamiya, 2016). In recent breeding for combined resistance to nematodes, potato virus Y and late blight has employed marker assisted selection (López et al, 2015, Milczarek et al, 2017. Asano et al (2012) evaluated potato varieties and lines by the multiplex PCR method, and 264 of 812 were positive for the H1 marker.…”
Section: Discussionmentioning
confidence: 99%
“…This trend has been supported by recent studies of the diversity of Russian potato cultivars and breeding lines using DNA markers of disease and pest resistance genes and cytoplasm types [6][7][8][9]. However, there is currently insufficient information to inform MAS efficiency at the early stages of breeding for pathogen resistance and on the effect of early selection on the manifestation of economically important traits in breeding material in field trial nurseriesA study using DNA markers linked to the resistance genes H1, effective against Globodera rostochiensis, Ry-fsto, effective against potato virus Y and Rpi-phu1 effective against LB in a segregating progeny did not reveal any relationship between the presence of various combinations of these markers and agronomical important traits, such as yield, size and shape of tubers [10]. The effectiveness of selecting prospective segregants with higher LB resistance upon the presence of the corresponding DNA markers has been studied but sporadically.…”
Section: Introductionmentioning
confidence: 93%